How can we describe impact of adult patient participation in health-service development? A scoping review. Issue 8 (August 2020) - Sandvin Olsson, Ann Britt; Strøm, Anita; Haaland-Øverby, Mette; Fredriksen, Kari; Stenberg, Una
Highlights: Patient participation in health-service development is not a common practice. Impact of patient participation in health-service development is understudied. The literature describes a broad variation of impacts from service development. Participatory health-service development leads to more patient participation. Our review can be of practical relevance to those conducting service development. Abstract: Objective: Patient participation represents a worldwide policy, but its impact lacks research. This study investigates impact of patient participation in health-service development by providing a comprehensive overview of how the literature describes it. Method: A scoping review with a broad search strategy was conducted. The literature was examined for study characteristics, purpose for, approaches to and impact of patient participation. The data were analyzed using a thematic analysis. Results: The 34 included primary studies reported impacts of patient participation that were interpreted to constitute two categories: 1. The participatory process´ impact on involved patient representatives and health professionals, and the organization´s patient participation practice itself. 2. The participatory service development´s impact on the design and delivery of services regarding patients and health professionals, and the organization. Conclusion: The literature describes a broad variation of impacts from health-service development, relevant for health professionals and patient representatives when initiating or participating in such processes. Our review provides an overview and discussion of these types of impact. Practice implications: The findings can be of practical relevance to those aiming to develop services, quality indicators regarding effects of patient participation, or to further investigate aspects of participatory service development.